2021
DOI: 10.3390/su13105657
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Social Support for a Sustainable Adolescence: A Theoretical Model of Its Sources and Types

Abstract: Despite the growing interest in perceived social support as a means of achieving sustainable psychological development and well-being in the various contexts of the adolescent, its definition and composition remain unclear. The aim of this study is to test both the hierarchical order and the types and sources of a theoretical model of the social support perceived by adolescents. The model is based on the theories of Tardy and Lin, as well as on the findings of recent studies on the construct. Three theoretical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 63 publications
1
2
0
Order By: Relevance
“…First, the results highlight the importance of family relationships to adolescent psychological well-being, in line with previous research showing that they can act as a protective factor or as a risk factor [63]. Furthermore, since family is considered one of the main educational agents promoting adolescent personal development [64], prevention and treatment programs should consider not only the involvement of family members but also training in conflict management skills. Second, our data showed that the assertive interpersonal schema plays a role in how family conflict has an impact on suicidal behaviour.…”
Section: Discussionsupporting
confidence: 85%
“…First, the results highlight the importance of family relationships to adolescent psychological well-being, in line with previous research showing that they can act as a protective factor or as a risk factor [63]. Furthermore, since family is considered one of the main educational agents promoting adolescent personal development [64], prevention and treatment programs should consider not only the involvement of family members but also training in conflict management skills. Second, our data showed that the assertive interpersonal schema plays a role in how family conflict has an impact on suicidal behaviour.…”
Section: Discussionsupporting
confidence: 85%
“…Third, empirical research on adolescents’ positive development showed that perceived social support mediates the link between positive parent–child relationships (i.e., development environment) and higher levels of social adaptation (i.e., positive development outcomes) ( Anan and Barnett, 1999 ; Pace et al, 2016 ). Thus, we conjecture that perceived social support, as an essential perceptual process of individuals ( Rodríguez-Fernández et al, 2021 ), mediates the relationship between school climate and prosocial behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Now, because external influences usually need to pass through own cognition and interpretation to be able to work, we believe that perceptions about own interpersonal relationships may have a helpful effect on behaviors ( Virtue et al, 2014 ); namely, individuals’ perceived social support may play an indispensable role in the engagement in prosocial behaviors, perhaps even one greater role than that of the environment. Two studies depicted this mechanism, demonstrating that perceived social support had a greater function on individuals’ behaviors than the environment ( Vaux, 1990 ; Rodríguez-Fernández et al, 2021 ). For instance, talking to friends about one’s troubles and emotions was far more supportive than just having a friend without communication.…”
Section: Introductionmentioning
confidence: 99%